Assigment of assets or provision of services?: The discrepant interpretation between the Tax Court and the Supreme Court of Justice of Lima regarding the determination of Income Tax in satellite services provided by non-domiciled subjects - Vera Carrión, Luis Fernando (2021)
The discrepancies between the Tax Court and the Supreme Court in tax matters are diverse and quite common, but, how can two different points of view change the tax treatment of an activity? The provision of satellite capacity provided by non-domiciled subjects is the topic of discussion in this article which will look at three cases in which both positions are observed, that of the Tax Court and the Supreme Court of Justice, as well as analyzing whether these transactions can be classified as services or transfer of goods and if this benefits constitutes income from Peruvian source subject to withholding tax on third-rate income. For this, we have resorted to the jurisprudence of botch the Fiscal Court and the Supreme Court of Lima, the Income Tax Law, the regulations about the provision of satellite capacity through geostationary satellites and the concepts provided in the Radiocommunications Regulations of the Union Telecommunications International.